Rock i Rörelse: Hardcore, Straight Edge, veganism och djurrättsrörelsen - Sandgren, Torgny (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
This article discusses the politics of music and the analysis of the cultural-theoretic perspectives, using the music genre of Hardcore and the Animal-Rights’ Movement in the city of Umeå in the 1990s as a case study. I analyze how a specific form of music becomes politicized and functions as the central driving force in a movement with political objectives. It is difficult to locate the dichotomy between Counter Culture and Sub Culture within this movement: Instead, it is better understood with the aid of Alberto Melucci’s concept of “New Social Movements”. The concept of “New Social Movements” focuses on the points of friction in late modern society; hence, analyses of the role of music in these movements may provide us with useful information on how music is being used by young people in order to understand, and deal with, the vital issues of present-day society.